2018
DOI: 10.1152/ajprenal.00638.2017
|View full text |Cite
|
Sign up to set email alerts
|

Nephron-specific knockout of TMEM16A leads to reduced number of glomeruli and albuminuria

Abstract: TMEM16A is a transmembrane protein from a conserved family of calcium activated proteins, which is highly expressed in the kidney. TMEM16A confers calcium-activated chloride channel activity which is of importance for various cellular functions in secretory epithelia and involved in secretion-dependent renal cyst growth. However, its specific function in renal physiology has remained elusive so far. Therefore we generated conditional nephron specific TMEM16A knockout mice and found that these animals suffered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…In contrast to He et al, we found that ongoing activation of ANO1 (or ANO6) by either ionomycin or purinergic stimulation increased intracellular Cl − concentrations in HEK293 and HeLa cells [102]. Nevertheless the proposed concept that intracellular Cl − levels determine vesicular endocytosis/exocytosis, control apical membrane delivery and morphogenesis [175], is interesting and corresponds well to the role of ANO1 in exocytosis and normal renal development detected in recent studies [107,175,176,177] (Figure 5). It is also noteworthy that intracellular Cl − regulation by ANO1 has been shown to participate in transcription of human epidermal growth factor receptor 2, which mediates PI3K/AKT/mTOR and JAK/STAT3 signaling pathways [52].…”
Section: The Role Of Anoctamins In Controlling Intracellular Cl− Csupporting
confidence: 72%
“…In contrast to He et al, we found that ongoing activation of ANO1 (or ANO6) by either ionomycin or purinergic stimulation increased intracellular Cl − concentrations in HEK293 and HeLa cells [102]. Nevertheless the proposed concept that intracellular Cl − levels determine vesicular endocytosis/exocytosis, control apical membrane delivery and morphogenesis [175], is interesting and corresponds well to the role of ANO1 in exocytosis and normal renal development detected in recent studies [107,175,176,177] (Figure 5). It is also noteworthy that intracellular Cl − regulation by ANO1 has been shown to participate in transcription of human epidermal growth factor receptor 2, which mediates PI3K/AKT/mTOR and JAK/STAT3 signaling pathways [52].…”
Section: The Role Of Anoctamins In Controlling Intracellular Cl− Csupporting
confidence: 72%
“…18,21 ). Along this line, it was shown that knockdown of TMEM16A during kidney development affects ciliogenesis and reduces the number of renal glomeruli, thus causing albuminuria 41,42 .…”
Section: Discussionmentioning
confidence: 97%
“…Inhibition of TMEM16A may also attenuate intestinal contraction and abdominal peristalsis (Sanders et al, 2012; Singh et al, 2014), and therefore could have antidiarrheal effects (Tradtrantip et al, 2010; Namkung et al, 2011b; Jiang et al, 2016). Finally, inhibition of renal TMEM16A could potentially lead to proteinuria and acidosis (Faria et al, 2014; Schenk et al, 2018). For activators of TMEM16A, opposite effects are possible, which is why local application via aerosol may be recommended for the treatment of CF lung disease.…”
Section: Biological Effects Of Inhibitors and Activators Of Tmem16amentioning
confidence: 99%